Conservative Treatment of an Infected Lateral Canal: A Case Report with a 4-Year Follow-up - Parirokh, Masoud; Hatami, Nima (Iranian Endodontic Journal, 2022)
Connective tissues in lateral canals mostly remain vital even after pulp necrosis of the main canals. However, lateral canals may become necrotic following the pulp necrosis of the main root canal or after root canal therapy. This case report presents a maxillary central incisor with a necrotic lateral canal and a sinus tract that initially showed healing following the primary endodontic treatment but showed infection after fiber-post placement and permanent restoration with composite resin. Tracing the sinus tract did not reveal the reason for the infection; however, cone beam computed tomography (CBCT) confirmed a lateral radiolucency of the maxillary right central incisor as the only reason for the return of the infection. A conservative re-treatment approach was performed, replacing the fiber post with gutta-percha and root canal sealer. Successful outcome was achieved with a conservative approach; however, it took some time for the sinus tract to heal. In the case of lateral canal infection, sealing the main root canal space could heal the lesion even without lateral canal negotiation. If the main root canal seal is disturbed, re-cleaning and obturating the main root canal could be successful